2020
DOI: 10.1097/hjh.0000000000002237
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of fully automated oscillometric central aortic blood pressure measurement techniques

Abstract: Background: Central aortic blood pressure (cBP) is a valuable predictor of cardiovascular risk. The lack of fully automated measurement devices impeded an implementation in daily clinical practice so far. The present study compares two novel automated oscillometric devices with invasively measured cBP. Methods: From March 2017 to March 2018, we enrolled consecutive patients undergoing elective coronary angiography to this cross-sectional study. Noninvas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 20 publications
2
31
0
Order By: Relevance
“…In agreement with our results, Gotzmann and colleagues [14] conducted a cross-sectional study of noninvasive central BP measurement by an oscillometric automated device (Mobil-O-Graph). It showed that the automated oscillometric monitors could assess central BP with acceptable accuracy.…”
Section: Discussionsupporting
confidence: 90%
“…In agreement with our results, Gotzmann and colleagues [14] conducted a cross-sectional study of noninvasive central BP measurement by an oscillometric automated device (Mobil-O-Graph). It showed that the automated oscillometric monitors could assess central BP with acceptable accuracy.…”
Section: Discussionsupporting
confidence: 90%
“…The mean difference was lower (−3 mm Hg) but dispersion was somehow larger than in general population. 10 , 11 The non-invasive metrics correlated well with the invasive ones, but correlation is not the intended statistic to consider when aiming a validation study. Having said this, the superior correlation with the central invasive pressure shown for the XCEL estimated central pressure with respect to the cuff-brachial SBP before TAVR would make it the first best candidate to be used in the calculation of non-invasive metrics related to the valvulo-arterial load in patients with AS.…”
Section: Discussionmentioning
confidence: 99%
“…8 (2) Bland-Altman analysis shows lower bias before and a larger bias after TAVR due to a more in- Nonetheless, this study did not fulfill the requirements of a validation study according to ARTERY Society protocols and in any case, the differences were outside the pass criteria. 8 The only appropriately powered and conducted validation studies for the XCEL device are Gotzmann et al 10 and Schultz et al 11 In the first study, including 502 patients, non-invasive assessment of aortic SBP was performed by both the SphygmoCor XCEL device and the Mobil-O-Graph NG device and was compared with simultaneous invasive pressure measurement (through fluid-filled catheters). The mean systolic bias of SphygmoCor XCEL device to invasively assessed aortic SBP was −5.0 ± 7.7 mm Hg and with Mobil-O-Graph NG device was slightly but significantly larger (−6.0 ± 10.4 mm Hg, p =.011).…”
Section: Pre-tavr Post-tavrmentioning
confidence: 99%
“…Regarding accuracy, many studies have sought to determine the accuracy of the Mobil‐O‐Graph 24h PWA device for measuring brachial BP, 9,10 central BP, 4,11 wave reflections, 12,13 estimated aortic pulse wave velocity, 14,15 and stroke volume 16,17 in adults. Taken together, all studies showed at least a reasonable agreement with the reference standard.…”
Section: Hemodynamic Variable Change From Daytime To Nighttime (“Dippmentioning
confidence: 99%